Expression of Interferon Effector Gene SART1 Correlates with Interferon Treatment Response against Hepatitis B Infection - Yong Li; Chuanlong Zhu; Faxi Wang; Tiantian Zhu; Jun Li; Shufeng Liu; Fei Xiao (Hindawi Limited, 2016)
Interferon-α (IFN-α) has limited response rate in the treatment of chronic hepatitis B (CHB). The underlying mechanism of differential responsiveness to IFN remains elusive. It has been recently reported that SART1 mediates antiviral effects of IFN-α in the hepatitis C virus (HCV) cell culture model. In this study, we investigated the role of SART1 in antiviral activity of IFN-α against hepatitis B virus (HBV) using blood and liver biopsy samples from chronic hepatitis B patients treated with pegylated IFN-α and HepG2 cells transfected with cloned HBV DNA. We observed that the basal SART1 expression in liver and PBMCs before IFN treatment was significantly higher in responders than in nonresponders. Furthermore, baseline SART1 expression level positively correlated with the degree of HBV DNA and HBeAg decline after IFN treatment. Mechanistically, silencing SART1 abrogated the antiviral activity of IFN-α, reduced the expression of IFN-stimulated genes (ISGs) Mx, OAS, and PKR, and attenuated JAK-STAT signaling in HepG2 cells, suggesting that SART1 regulates IFN-mediated antiviral activity through JAK-STAT signaling and ISG expression. Our study elucidates the important role of SART1 in IFN-mediated anti-HBV response and provides new insights into understanding variation of IFN treatment response in CHB patients.